2021
DOI: 10.1016/j.ekir.2021.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Analysis Reveals Complexity of Monogenic Urinary Stone Disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 95 publications
1
9
0
Order By: Relevance
“…Interestingly, identified molecular diagnoses pertained to only three distinct disorders: (a) cystinuria, (b) dRTA, and (c) renal phosphate wasting. Analogous to previous data on adult and adolescent cohorts, dominant genes predominated their recessive counterparts (Braun et al, 2016;Cogal et al, 2021;Halbritter et al, 2015). While in cystinuria both modes of inheritance were observed, we only found…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, identified molecular diagnoses pertained to only three distinct disorders: (a) cystinuria, (b) dRTA, and (c) renal phosphate wasting. Analogous to previous data on adult and adolescent cohorts, dominant genes predominated their recessive counterparts (Braun et al, 2016;Cogal et al, 2021;Halbritter et al, 2015). While in cystinuria both modes of inheritance were observed, we only found…”
Section: Discussionsupporting
confidence: 88%
“…However, the question of whom to subject to genetic testing is still unresolved. Most of the previous studies focused on childhood KSD (Braun et al, 2016; Cogal et al, 2021; Daga et al, 2018) and available prevalence data is difficult to interpret. A main limitation of most studies constitute their preselection of patients based on an upfront clinical suspicion of monogenic KSD (Cogal et al, 2021; Halbritter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others identified that diagnosable phenocopy disorders may be more common, representing up to one in five genetic diagnoses in suspected hereditary kidney disease and that an approach rigidly applying very strictly targeted gene panels rather than broader or cascade panels does not identify such instances [ 30 ▪ ]. For complex phenotypes such as urinary stone disease, the evidence for broadened gene panels is further reflecting this concept that application of a very targeted gene panel approach will fail to identify a genetic diagnosis that is present and directly related to the patient phenotype in 10–20% of instances [ 31 ].…”
Section: New Indications For Genomic Testingmentioning
confidence: 99%
“…Twenty-three patients were referred for molecular diagnosis to the Laboratory of histomorphology and molecular biology of the kidney (Italy) and 12 were referred to the Rare Kidney Stone Consortium (RKSC) in the USA. Sanger sequencing was used to determine and verify the pathogenic variants in OCRL in our cohort [16]. OCRL variants were classified as pathogenic or likely pathogenic according to American College of Medical Genetics and American College of Pathologists (ACMG/AMP) guidelines [17].…”
Section: Subjectsmentioning
confidence: 99%